Therapeutic mucosal vaccination of herpes simplex virus type 2 infected guinea pigs with an adenovirus-based vaccine expressing the ribonucleotide reductase 2 and glycoprotein D induces local tissue-resident CD4+ and CD8+ TRM cells associated with protection against recurrent genital herpes - Quadiri, Afshana; Prakash, Swayam; Vahed, Hawa; Tadros, Jimmy Medhat; Sun, Miyo; Hormi-Carver, Kathy K.; Patel, Swena Jignesh; BenMohamed, Lbachir (Frontiers in Immunology, 2025)
IntroductionThe reactivation of herpes simplex virus 2 (HSV-2) from latency causes viral shedding that develops into recurrent genital lesions. The role of tissue-resident T cells and the nature of viral antigens associated with protection against recurrent genital herpes remain to be fully elucidated.MethodsIn this preclinical study, we investigated the protective therapeutic efficacy, in the guinea pig model of recurrent genital herpes, of five recombinant adenovirus-based therapeutic vaccine candidates (rAd-Ags), each expressing different HSV-2 envelope and tegument proteins: RR1 (UL39), RR2 (UL40), gD (glycoprotein D), VP16 (UL48), or VP22 (UL49). We compared the frequency and function of dorsal root ganglia (DRG)- and vaginal mucosa (VM)-resident CD4+ and CD8+ T cells induced by each vaccine and their effect on the frequency and severity of recurrent genital herpes. ResultsHSV-2 latent-infected guinea pigs immunized with rAd-RR2 and rAd-gD vaccines showed high frequencies of DRG- and VM-tissue-resident IFN-g-producing CD4+ and CD8+ TRM cells associated with significant reductions in viral shedding and genital herpetic lesions.DiscussionTaken together, these preclinical results provide new insights into the T cell mechanisms of protection against recurrent genital herpes and confirm the tegument RR2 protein and glycoprotein D as viable candidate antigens to be incorporated in future genital herpes therapeutic vaccines.